A Canadian Study toward Changing Local Practice in the Diagnosis of Pediatric Celiac Disease. (26th April 2016) - Rajani, Seema; Huynh, Hien Q.; Shirton, Leanne; Kluthe, Cheryl; Spady, Donald; Prosser, Connie; Meddings, Jon; Rempel, Gwen R.; Persad, Rabindranath; Turner, Justine M.
Abstract : Background . The European Society for Pediatric Gastroenterology, Hepatology and Nutrition endorses serological diagnosis (SD) for pediatric celiac disease (CD). The objective of this study was to pilot SD and to prospectively evaluate gastrointestinal permeability and mucosal inflammation at diagnosis and after one year on the gluten-free diet (GFD). We hypothesized that SD would be associated with similar short term outcomes as ED. Method . Children, 3–17 years of age, referred for possible CD were eligible for SD given aTTG level ≥200 U/mL, confirmed by repeat aTTG and HLA haplotypes. Gastrointestinal permeability, assessed using sugar probes, and inflammation, assessed using fecal calprotectin (FC), at baseline and after one year on a GFD were compared to patients who had ED. Results . Enrolled SD (n = 40 ) and ED (n = 48 ) patients had similar demographics. ED and SD groups were not different in baseline lactulose: mannitol ratio (L : M) (0.049 versus 0.034;p = 0.07 ), fractional excretion of sucrose (%FES; 0.086 versus 0.092;p = 0.44 ), or fecal calprotectin (FC; 89.6 versus 51.4;p = 0.05 ). At follow-up, urine permeability improved and was similar between groups, L : M (0.022 versus 0.025;p = 0.55 ) and %FES (0.040 versus 0.047;p = 0.87 ) (p > 0.05 ). FC improved but remained higher in the SD group (37.1 versus 15.9;p = 0.04 ). Conclusion . Patients on the GFD showed improved intestinal permeability and mucosal inflammation regardless of diagnostic strategy. This prospective study supports that children diagnosed by SD have resolving mucosal disease early after commencing a GFD.